Biaya Ekuitas dan Nilai Perusahaan: Apakah Pengungkapan Karbon Berpengaruh? - Padma, Niluh; Rahmawati, Isna Putri (Accounting Global Journal, 2025)
This study aims to obtain empirical evidence on the impact of carbon disclosure on the cost of equity and firm value. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2020-2022. A purposive sampling technique was used to select the final sample of 386 observation data from 129 companies (unbalanced panel data). This study has two dependent variables: cost of equity measured by the PEG ratio and firm value measured by Tobin's Q. Data analysis using multiple linear regression techniques. The results of the study indicate that carbon disclosure has a positive effect on the cost of equity. In addition, carbon disclosure also has a positive impact on firm value.